Writing performance and moral reasoning in business education? - Johnson, J. Lynn (Journal of business ethics, 1993)
This study investigates the connection of moral reasoning to demographic and performance variables in business education, especially business and technical writing. The moral reasoning construct serves as the foundation for one's decision making when confronted with moral dilemmas. Significant relationships are reported between subjects' writing skill and their moral reasoning scores. This research serves as a foundation for questions about writers' moral reasoning and the ethical decisions each writer makes in written communication. In addition, this study supports further research into the connection between moral reasoning and written communication, given the significant relationships reported and the noticeable shortage of related, data-based research.